2013 Cotton Defoliation and Harvest Aid Guide - Ramon Leon; David L. Wright; Barry J. Brecke (EDIS)
In Florida, cotton requires about 155 days of growth from planting to harvest. Throughout the growing season, growers must make important management decisions about defoliation, boll opening, and regrowth suppression. These factors can affect the quality and storage time if the crop is put into modules. The greatest losses in quality are caused by stain from poorly defoliated plants or regrowth and moisture from green tissue. This 8-page fact sheet was written by R.G. Leon, D. L. Wright and B. J. Brecke, and published by the UF Department of Agronomy, October 2013.